Duets [compact disc] : re-working the catalogue - Morrison, Van, 1945- (RCA Records, 2015)
Van Morrison releases the 35th album of his storied career. Here he has re-recorded some of his favorite songs with the help of fellow artists including Michael Buble, Mavis Staples, and his own daughter Shana Morrison.